Word final prolongations: acoustic characteristics and influence on speech fluency perception - Souza, Lívia Maria Santos de; Martins-Reis, Vanessa de Oliveira; Santos, Pâmela Jesus dos; Gomes, Dianete Ângela do Valle; Lima, Aveliny Mantovan Lima; Celeste, Letícia Correa (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
The aim of this study was to characterize word final prolongations in individuals with and without stuttering as well as to investigate the influence of end of words prolongations on speech fluency perception. In Experiment 1, 14 subjects were submitted to speech fluency evaluation for analysis of duration and average frequency of extended phones at the end of words. In Experiment 2, twenty lay judges were asked to judge the fluency degree of utterances without disfluency, utterances containing prolongations and utterances containing filled pauses. In experiment 1 the groups differed only in the duration’s variation; in both groups the prolongations in monosyllabic words prevailed; 80% of the prolonged phones in both groups were vowels. In experiment 2 no significant difference was found in the comparison between the judgements of prolongations and filled pauses. The utterances without disfluency differentiated themselves significantly from the others. We suggest that characteristics such as position in the word, duration and physical concomitants should be considered before deeming prolongations as a stuttering-like disfluency.